INDICATORS OF OPTIMAL SYSTEMIC HEMODYNAMICS IN LOWER LIMB JOINT ARTHROPLASTY IN PATIENTS WITH HIGH ANESTHETIC RISK WITH UNILATERAL SPINAL ANESTHESIA COMBINED WITH UNILATERAL EPIDURAL ANALGESIA - Rakhmankulov Eldor Djurakulovich; Matkurbanov Khudoyishukur Makhsadbaevich; Yusupova Bahtigul Yusupovna; Yusupova Nihola Shavkatovna; Boltaev S.R. (Scholar Express Journals, 2022)
Regional anesthesia (SA, EA) is often preferred in operations on the lower extremities in order to induce the necessary sensory block with minimal impact on the sympathetic nervous system [184; pp.105-115]. The goal of unilateral SA is to limit the spread of somatic and sympathetic blockade [146; pp. 2379-2402], which provides a number of clinical advantages and, above all, in reducing hemodynamic complications [83; pp. 298-311] and is useful in geriatric patients with a hypodynamic circulation regime with low cardiac output, which are the patients we are studying
Keywords: Epidural anesthesia; comorbidity index; randomized clinical trial.